Bacterial Black Spot (BBS) of Mango in Florida - Jonathan Henry Crane; Romina Gazis (EDIS)
Bacterial black spot, caused by the bacterium Xanthomonas citri pv. mangiferaeindicae, is a relatively new (~2015) bacterial disease in Florida that has the potential to limit mango production of some cultivars. This new 6-page fact sheet provides the current knowledge and status of the disease potential on various cultivars. Written by Jonathan Crane and Romina Gazis, and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1369